RGEC Sebagai Metode Analisis Kesehatan Bank (Studi Kasus Pt Bpr Pijer Podi Kekelengen) - Hutagalung, Cindy Ruth Putri Angelia; Nurlinda, Nurlinda (Jurnal Ilmiah Akuntansi Keuangan dan Bisnis (JIKABI), 2024)
This Final Report is entitled "RGEC as a Bank Health Analysis Method (Case Study of PT BPR Pijer Podi Kekelengen)".The purpose of this Final Report is to determine the health level of PT BPR Pijer Podi Kekelengen for the 2018-2022 period using the RGEC method. The reason this title was chosen was because it saw the phenomenon of weak public trust in BPR and in order to increase public trust and also considering the importance of bank health assessment. The population in this Final Report is the financial statements of PT BPR Pijer Podi Kekelengen and the sample in this Final Report is the financial position report, income statement, productive asset quality report and governance implementation report of PT BPR Pijer Podi Kekelengen for the 2018-2022 period. The type of data used in this Final Report is quantitative data with data sources, namely secondary data, using data collection techniques, namely documentation techniques through the Financial Services Authority website. The data processing technique used is descriptive technique using the RGEC method. Based on the results of data analysis, it can be concluded that PT BPR Pijer Podi Kekelengen for the 2018-2022 period is in the range of Composite Rating (PK) 1 or very healthy and Composite Rating (PK) 2 or healthy. This reflects that PT BPR Pijer Podi Kekelengen is able to deal with the negative effects of changes in conditions that may occur.